‘Children and fools, they say, cannot lie’: un dicton tourné en plaisanterie dans Misogonus d’Anthony Rudd - Pauline Blanc (Revue LISA)
In the play entitled Misogonus that is attributed to Anthony Rudd by one of its editors, Lester E. Barber, the Vice-character, Cacurgus, stands out as a virtuoso performer even though he merely demonstrates a moral lesson. The double-dealing servant of two masters, Cacurgus goes out of his way to prove the ill-founded premises of the saying “Children and fools, they say, cannot lie”. He deceives both of his masters, but remains loyal to his audience for whom he performs a highly entertaining play. The two aspects of his role are shown to be quite distinct as he intervenes on the outside and inside of two separate plots in which the twists and turns of a devious mind are displayed as being a series of disagreeable tricks played upon a group of malleable, credulous victims.